Redefining roles in wheelchair basketball: A data driven approach to characterising playing positions - Wilde, P.; Santos-Fernandez, E.; Peeling, P.; Mitchell, L.; Denman, S. (Journal of Sports Sciences, 2026)
A key facet of wheelchair basketball is the sport classification system, where players are assigned scores from 1.0 to 4.5 (where lower scores indicate greater activity limitation for wheelchair basketball related tasks), and on-court lineups cannot exceed a total of 14 sport classification points. In wheelchair basketball, the specific on-court roles of players are poorly understood outside of labelling players into sport classification categories or likening them to traditional running basketball positions. This study presents a data-driven approach to characterising playing positions in elite, male wheelchair basketball using Gaussian Mixture Model analysis. Box score metrics describing players on-court actions from 12 men`s international tournaments between 2019-2024 were analysed, totalling 5265 match statistics from 342 players across 304 matches. The model identified six novel and diverse player roles. These ranged from primary playmaker and dynamic impact roles that higher classification players (3.5-4.5) tended towards, to off-ball, defensive orientated roles which lower classification players (1.0-1.5) were frequently observed in. This research provides a novel framework for understanding player roles that accounts for the sport`s unique characteristics. This has significant implications for refining player selection in response to lineup needs, informing player recruitment for balanced team building and improving targeted player development pathways.